Session-RPE for quantifying load of different youth taekwondo training sessions - Lupo, C.; Capranica, L.; Cortis, C.; Guidotti, F.; Bianco, A.; Tessitore, A. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The session rating of perceived exertion (session-RPE) proved to be a valuable method to quantify the internal training load (ITL) in taekwondo. However, no study validated this method in youth taekwondo athletes performing different training sessions. Thus this study aimed at evaluating the reliability of the session-RPE to monitor the ITL of prepubescent taekwondo athletes during pre-competitive (PC) and competitive (C) training sessions.